Study of the Chemical Activity of Metal Powders Based on Aluminum, Boron and Titanium; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Korotkikh A. G. Aleksandr Gennadievich (2020, 2020)
Title screen